Is ISO20121 Certification a Detour or Gamechanger for Eco-Striving Sport Events? A Conceptual Typology - Næss, Hans Erik (Frontiers in Sports and Active Living, 2021)
An increasing number of sport organizations express interest in international accreditation standards as a way of tackling environmental sustainability challenges. This article however argue that the commercial context of these standards and “the bazaar economy” in which its suppliers operate may hamper the diverse solutions needed to reduce the ecological footprint of sport. At the same time it acknowledges that standards are useful to certain sporting organizations. To sort out the pros and cons of the relation between such standards and environmental sustainability (ES) work in sport organizations the Formula E (for Electric) championship is used as case example. The championship became the first category in motorsport to receive ISO certification in 2018, and two years later it achieved net zero carbon footprint from inception. On that basis, the article provide a typology that provide coordinates for empirical research on how sport organisations may avoid “organizational hypocrisy” in their ES work by viewing the pros and cons of ISO certification. While the practical implication is insight in what it takes for a sport organization to achieve a specific certification, the academic implication is conceptual coordinates for empirical and comparative research of ES initiatives and certifications.